PEMANFAATAN TEMPURUNG BIJI KARET (Havea Brasiliensis) SEBAGAI BAHAN ALTERNATIF DALAM PENGOLAHAN LIMBAH TEKSTIL - Nur Linda Anggraini; Saibun Sitorus; Rahmat Gunawan (PROSIDING SEMINAR KIMIA, 2018)
The utilization of rubber seed shell (Havea Brasiliensis) can be used as an alternative material in the processing of textile waste. The next step to determine the efficiency of a material rubber seed shell performed experiments of material in process with the addition of material rubber seed shell by variations of concentrations 2 grams, 3 grams, 4 grams and 5 grams per 200 mL sample for each parameters. Then stirred at 100 rpm for 15 minutes and then deposited for 24 hours. Based on the final results obtained for TSS (Total Suspended Solid) parameter removal efficiency is 97,40%. for the Cr metal ion parameter is 62,39% and for Cu metal ion is 68,65%. For efficiency of dyes parameter is 70,72% with optimum concentration of material is 5 grams for each parameters. Keywords: Rubber seed shell, TSS, metal ion, dye.